Strategi Komunikasi Dinas Perpustakaan dan Kearsipan Kabupaten Bangkalan dalam Meningkatkan Literasi Pemustaka Usia Sekolah - Fani, Meithia; Alamiyah, Syifa Syarifah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Literacy in Indonesia is relatively low at 0.001 percent. Referring to literacy data from East Java Province, Bangkalan Regency has a level of reading interest (TGM) of 67,2. As a strategy to increase the literacy of school-aged users, the Department of Library and Archives Regency Bangkalan carried out several program stages. This research aims to find out how the communication strategy of the Bangkalan Regency Library and Archives Service improves the literacy of school age users. The method used in the research is a descriptive qualitative method by collecting observation data and in-depth interviews with staff, librarians and school age users. The results of this research indicate that to increase the literacy of school-age users at the Department of Library and Archives Regency Bangkalan, they have implemented a communication strategy which was analyzed using a five-step strategy model. Apart from that, specific strategies to increase literacy consist of 4 forms, namely Internal (Library Development Training and TPBIS Development), External (BangLabang, Kubiling, eBecah, Library Visits, Literacy Seminars, Selection of Literacy Ambassadors, and Storytelling Competitions), Digital (Social media management: Instagram, Facebook, Youtube, and TikTok), and Collaboration (Bangkalan Children's Forum and PT Gramedia).